Asian Stereotypes: Asian Representation in Hollywood Films - Sriganeshvarun, Nagaraj; Chien, Puu Wen (INTI International University, 2020)
Asian stereotypes in Hollywood films is a topic that always discussed by the public. For decades, the leading roles in Hollywood films are always played by white actors, and the criminal roles are played by actors with colour, such as Asians. Asians are always lack of representation or being portrayed negatively in Hollywood films. However, as time pass by, the representation of Asians started to improve in the 21st century. The purpose of this study was to analyse about the stereotypical images of Asians, understand the relationship between Asian and American characters in Hollywood films, and to explore about how the Asians representation have changed in Hollywood films from 1960s till now. The data was collected by using qualitative research method. Textual analysis was used to conduct the findings, which comprised six selected films namely, Breakfast at Tiffany’s (1961), Sixteen Candles (1984), Rush Hour (1998), Shanghai Noon (2000), The Hangover (2009), and Pitch Perfect (2012).